МОДЕРНІЗМ В УКРАЇНСЬКІЙ КУЛЬТУРІ КІНЦЯ ХІХ ст. – ПОЧАТКУ XX ст. - Фільова, Т. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
У статті аналізується модернізм в українській культурі кінця ХІХ ст. − початку ХХст. Розглядається поняття «модернізм» з позиції культурології. Аналізуютьсяпередумови появи модернізму в культурі. Виділяються особливості українськогомодернізму. З’ясовується роль модернізму в розвитку української культури.Ключові слова: модернізм, українська культура, новаторська культура.Филёва Т. В. Модернизм в украинской культуре конца ХІХ ст. – начала ХХ ст.В статье анализируется модернизм в украинской культуре конца ХІХ ст. – начала ХХ ст.Рассматривается понятие «модернизм» с позиции культурологии. Анализируютсяпредпосылки появления модернизма в культуре. Выделяются особенности украинскогомодернизма. Определяется роль модернизма у развитии украинской культуры.Ключевые слова: модернизм, украинская культура, новаторская культура.Fileva T. V. Modernism in the culture of Ukrainian end XIX - the beginning of XXcentury. This paper presents and analyses the modernism in the culture of Ukrainian end XIX– the beginning of XX century. Concepts of «modernism» with position of culturology areconsidered. Preconditions of appearance modernism in the culture are analyzed. Peculiaritiesmodernisms of Ukrainian are emphasized. Role of modernism in the development culture ofUkrainian are defined.Key words: modernism, culture of Ukrainian, innovation culture.